Analisis Adopsi Continuous Auditing pada Fungsi Audit Intern di Lembaga Negara XYZ - Rahayu, Sri; Prasetya, Machmudin Eka (Owner : Riset dan Jurnal Akuntansi, 2024)
This research is motivated by the challenges faced by the Internal Audit Function (IAF) at XYZ Government Institution in the midst of the rapid development of technology and financial transactions that have been fully digitized using the Enterprise Resource Planning / Human Resources Information System. In order to utilize financial transaction data and technology, IAF carries out digital transformation by adopting continuous auditing and developing the Pemantauan Off Site Risiko Operasional (PERISAI) application as a continuous auditing implementation tool. The purpose of this study is to analyze the suitability of the steps taken by the IAF at XYZ Government Institution in adopting continuous auditing based on the Global Technology Audit Guide (GTAG) 3: Coordinating Continuous Auditing and Monitoring to Provide Continuous Assurance (2nd edition), analyzing the success of the PERISAI application based on the user's perspective using the DeLone and McLean Information System Success Model. This research uses a case study research strategy with an exploratory study method. The data collection methods used were semi-structured interviews consisting of open and closed ended questions, documentation, and observation. The results of this study indicate that the steps taken by FAI to implement continuous auditing are not fully in accordance with the key steps for implementing continuous auditing in GTAG 3 (2nd edition), while the PERISAI application is considered successful by FAI internal auditors even though there are still some things that must be improved from the aspects of people, process, and technology used.